Infodemics and its Effect on Mental Health of Medical Students of IMDC during COVID-19 Pandemic - Noor-ul-Ain Irfan , Iman Afraz , Farah Rashid , Sadia Yasir , Irfan Afzal Mughal , Asma Irfan (Journal of Rawalpindi Medical College, 2021)
Introduction Globally rising the number of daily COVID-19 cases has triggered the incredible surge in the information (and misinformation) regarding COVID-19. This misinformation was about numbers of cases, inaccurate guidelines, advertisement of unapproved treatments, and remedies as cures. The increasing prevalence of depression and anxiety was found to be linked directly to the misinformation catered from social media. The study aims to explore the mental health of medical students due to a surge in information and misinformation regarding Covid-19. Materials and Methods This cross-sectional study was conducted online from August 2020 to January, 2021. 227 MBBS students of IMDC (1st year to final year with age range 19-25 years) were invited to participate in an online survey through Google docs. Those who were on medication for anxiety and depression were excluded from the study. The use of the data for research purposes was explained and written consent in the first section of the online survey was given to all participants before filling the questionnaire which was divided into 3 sections. The first part was about Demographic information. The second part consisted of 5 questions about info-media use and the third part consisting of 12 questions about mental health including stress-related and behavioral changes, somatic symptoms, emotional disturbance, and cognitive functioning during the covid-19 pandemic. Ethical Approval was taken from the ethical committee of IMDC. A Chi-square test was applied to calculate the significance of qualitative variables and determine the prevalence of mental health. Results The total number of students who participated in this survey were 227 (28.2% males and 71.8% females). Among types of info-media, Whats-app was used most frequently by MBBS students. Different questions were asked regarding Info-media usage and mental health. A significant association was found between gender (Both males and females) and feelings of fear and worry (p-value 0.004**), feeling socially isolated(p= 0.005**), difficulty in communicating with people (p = 0.021*), feeling confused in decision making as time progressed( 0.008**), lack of interest in studying or difficulty in concentration during this time (p 0.037*) and effect on memorizing ability (0.000)**.MBBS students who were regularly using Info-media showed a significant disturbance in mental health problems including stress-related and behavioral changes and somatic symptoms. They were found to be significantly fearful and worried (p-value 0.010*), had difficulty in communicating with people regarding covid-19(p-value 0.021*), and also felt a change in appetite-valuable 0.030*). No serious mental health problem was found related to cognitive functioning. Conclusion In conclusion, our findings show that there is a high prevalence of mental health problems, which were positively associated with frequent use of info-media during the COVID-19 outbreak.